How to build total quality management system for higher education in a small country - Violeta Milenkovska; Blagica Novkovska (UTMS Journal of Economics, 2019)
In this paper the issue of effective establishment of total quality management system in higher education in Macedonia is discussed in details. In Macedonia, substantial changes occurred during last two decades: introduction of Bologna system, establishment of private higher education institutions, accompanied by multiple changes of the respective state regulation. After a period of intensive changes, actual state of the higher educational system is relatively stable, allowing introduction of largely applied quality management system intended to be used in future on long term. On central level, particular role is expected to be played by the higher education Quality Agency, responsible for the accreditation and evaluation of higher education in Macedonia, according the new low. Effective system has to produce value for all stakeholders. Authors consider that in the next period optimal conditions will be in place to introduce uniform total quality management system which will support accelerated improvement of the quality of higher education services.
Keywords: I21; I29; K39; M3; 330; quality management; higher education; business process modelling